Civilians under missile attack: post-traumatic stress disorder among the Jewish and Bedouin population of Southern Israel - Rachel Shvartsur; Bella Savitsky (BMC, 2024)
Abstract Background Over the past 20 years, Jewish and Bedouin civilians in southern Israel have faced the ongoing threat of missile attacks from Gaza, with possible mental health consequences. This study aimed to assess the prevalence of post-traumatic stress disorder (PTSD) among Jewish and Bedouin adult civilians in southern Israel in a period with few missile attacks from Gaza, and no military operations. Methods The study population included 389 participants (246 Jews, 143 Bedouins) living within 40 km/25 mi from Gaza for at least 2 years and interviewed between January and March 2023 (before the ongoing war that started on October 7th, 2023). The PTSD Checklist (PCL-5) was used, with a score of 33 as a cutoff point for the presence of PTSD. Results Compared to Jews, a significantly lower proportion of Bedouins reported accessibility to bomb shelters and siren warning systems. Overall, 20.3% of the respondents exhibited PTSD. Multivariate analysis revealed that after adjustment for demographic and household characteristics, Bedouins had a six-fold significantly higher probability of PTSD in comparison to Jews (OR 5.6, 95%CI 2.8-10.8). Compared to participants with high socioeconomic status (SES), participants with low SES had a six-fold significantly higher probability of PTSD (OR 6.0, 95%CI 2.2-16.5). Participants who did not have an alarm system had more than two-fold odds for PTSD (OR 2.3, 95%CI 1.1-5.5). Being single, living in urban areas, or having a disability significantly increased the probability of PTSD. Conclusions The findings of this study demonstrate a significantly higher prevalence of PTSD among the Bedouin population of Southern Israel. Several sociodemographic characteristics were associated with the increased prevalence of PTSD, the most prominent of which was low SES. Healthcare professionals and authorities should be proactive in screening for PTSD, and provide tailored treatment and support, taking into account ethnical and cultural background. Authorities should address the disparity in bomb shelter access and siren warning coverage between Bedouin and Jewish communities.